“About taste with taste” – did Jan Matejko receive black soup, who was Czarny Strzelec, where the painter drank the best coffee...? - Kłak-Ambrożkiewicz, Marta (Perspektywa stołu, 2023)
The sketch was prepared on the basis of a series of meetings “About taste with taste” conducted by the author in 2017 at the Jan Matejko House biographical Museum in Krakow in cooperation with the Lesser Poland Heritage of Taste Association. In the text we will find answers to several questions: did Jan Matejko receive black soup, as it used to be at the Matejkos in Krzesławice, and who was the mysterious Black Sagittarius? For dessert, a story about lipsticks from Redolfi and black coffee was recalled. Thus, it is a kind of return through manuscripts, diaries and memories related to the outstanding Polish master of the paintbrush to the roots of Krakow’s culinary identity in the second half of the 19th century.